2023
DOI: 10.1002/cncy.22772
|View full text |Cite
|
Sign up to set email alerts
|

Molecular‐derived risk of malignancy and the related positive call rate of indeterminate thyroid cytology diagnoses as quality metrics for individual cytopathologists

N. Paul Ohori,
Jacqueline M. Cuda,
Sheldon I. Bastacky
et al.

Abstract: BackgroundIndeterminate thyroid cytopathology diagnoses represent differing degrees of risk that are corroborated by follow‐up studies. However, traditional cytologic–histologic correlation may overestimate the risk of malignancy (ROM) because only a subset of cases undergo resection. Alternatively, some molecular tests provide probability of malignancy data to calculate the molecular‐derived risk of malignancy (MDROM) and the positive call rate (PCR). The authors investigated MDROMs and PCRs of indeterminate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…5 We also analyzed the relationship between the AUS:M ratio and TSV3 PCR, using the framework established by Cibas et al 20 for ASCUS:SIL ratios and high-risk HPV positivity rates in gynecologic cytology. Moreover, we examined the relationship between the AUS:M ratio and MDROM, using the MDROM as a surrogate of the ROM, as highlighted by Ohori et al 23 Additionally, we investigated the relationship between the AUS:M ratio and ROM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 We also analyzed the relationship between the AUS:M ratio and TSV3 PCR, using the framework established by Cibas et al 20 for ASCUS:SIL ratios and high-risk HPV positivity rates in gynecologic cytology. Moreover, we examined the relationship between the AUS:M ratio and MDROM, using the MDROM as a surrogate of the ROM, as highlighted by Ohori et al 23 Additionally, we investigated the relationship between the AUS:M ratio and ROM.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation of AUS rates with MT results has been put forward as a QA metric tool to attain the target rate of 10%. 9,21,22 Furthermore, Ohori et al 23 recently demonstrated that the MDROM could be used as a feedback tool to provide potential strategies for practice improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation